Comparative Evaluation Of The Obturating Quality Of Three Different Endodontic Rotary File Systems Using Cbct – An In-Vitro Study - Kumar, Prawal; Sharma, Deepak; Agrawal, Shyam; Mathur, Rachit; Doshi, Meenal; Digantic, W (Journal of Neonatal Surgery, 2025)
Introduction: Efficient cleaning or shaping of root canal system are vital for successful endodontic treatment, ensuring optimal obturation and minimizing microleakage. Aims & Objectives: This in vitro research aims to compare quality of obturation by utilizing 3 rotary file systems—Coltene Gen Z, ProTaper Next, Neo Endo S—with CBCT (cone-beam computed tomography) analysis. Materials & Methodology: Forty-eight extracted single-rooted mandibular premolars have been separated into 3 groups (n=16) and instrumented using the respective file systems with an XPEDENT endomotor. Irrigation has been conducted by utilizing 5.25 percent sodium hypochlorite as well as 17 percent EDTA. Canals have been obturated with AH Plus sealer or gutta-percha using lentulospirals and hand pluggers. Result: Obturation quality was assessed using RVG and CBCT, and data were analyzed using SPSS v17.0. Results showed ProTaper Next had highest percentage of acceptable obturation (87.5 percent) or density (93.75%), followed by Coltene Gen Z (62.5%) and Neo Endo S (50%). Conclusion: ProTaper Next demonstrated superior shaping and obturation efficacy compared to Coltene Gen Z, Neo Endo S, indicating its clinical advantage in endodontic procedures.